420 Impact of Surgical Training on Long-Term Patient Outcomes in Sleeve Gastrectomy. (12th October 2021) - Ghosh, A; Lo, C; Reddy, M; Khan, O
Abstract: Aim: Although few studies have examined the impact of surgical training on early postoperative outcomes in bariatric surgery, there is limited data on longer-term outcomes in trainee-performed cases. Our aim was to evaluate the effect of surgical training on weight loss outcomes following laparoscopic sleeve gastrectomy (LSG). Method: Data was prospectively collated on patients undergoing primary LSG at a Quaternary Bariatric London teaching Hospital between 2016-2017. Inclusion criteria was BMI≥35. Exclusion criteria were BMI<35 or > 60, planned HDU admission and LSG with concomitant hiatus hernia repair. Operative time, length of stay, complications and longer-term excess weight loss was recorded with outcomes of consultant and trainee cases compared. Results: 76 LSG patients were included; 44 performed by consultants, 32 by trainees. There was no difference in age, gender, pre-operative weight, BMI and number of obesity-related comorbidities between groups. Operative time (trainee105±10.0 vs consultant91±18.1 mins) and length of stay (trainee2.6±0.4 vs consultant2.8±0.9 days) were similar between groups. There were 3 complications in the trainee group (intra-abdominal collection requiring drainage, wound infection, hypokalaemia); and 2 with consultants (wound infection, intra-operative bleeding with ICU admission). Excess Weight Loss(%) at 2 years was 55.9%±7.5% for trainee cases and 52.4%±6.7% for consultant cases( p =0.49). Excess Weight Loss(%) at 3.5 years was 54.9%±9.9% for trainee cases and 50.7%±9.9% for consultant cases( p =0.54). Conclusions: Outcomes in trainee performed LSG are comparable to those performed by consultants. Surgical training in a high-volume teaching hospital does not appear to have detrimental effect on patient outcomes following LSG.